A policy, a ‘priority’, an unfinished project: The Ontario First Nation, Métis, and Inuit Education Policy Framework - Currie-Patterson, Natalie; Watson, Kaitlyn (Comité canadien des étudiants diplômés en éducation, 2017)
In 2007, the Ontario Ministry of Education released the Ontario First Nation, Métis, and Inuit Education Policy Framework. The policy set forth a vision to significantly improve the levels of achievement for Indigenous students attending Ontario’s public schools, and to increase awareness and knowledge of Indigenous cultures and perspectives for all students by the year 2016. Drawing upon critical pedagogy, theories of decolonizing education, and policy enactment, we engaged with the Framework and a set of related documents to a critical discourse analysis. Four discourses were revealed: achievement; increasing capacities; incorporating “cultures, histories, and perspectives”; and absence. In tracing the presence of these discourses across the documents we found that, while well-intentioned, the policy has yielded problematic outcomes. In turn, this undermines the ability of Ontario’s education system to not only reach the aforementioned goals but also to take an active role in reconciliation and efforts towards the decolonization of education.